Case Report: SARS-CoV-2 Infection—Are We Redeemed? A Report of Candida Spondylodiscitis as a Late Complication - Moreno-Gómez, Luis Miguel; Esteban-Sinovas, Olga; García-Pérez, Daniel; García-Posadas, Guillermo; Delgado-Fernández, Juan; Paredes, Igor (Frontiers in Medicine, 2021)
Background: We describe a case of candida spondylodiscitis secondary to COVID-19. Case report: A 47-year-old man diagnosed with SARS-CoV-2 required prolonged admission to the ICU. Four months later, he was diagnosed with thoracic candida spondylodiscitis. Medical management was insufficient, so he eventually underwent surgery. Discussion: Fungal infections seem to be more likely in patients with COVID-19, but it is unknown whether they are directly attributed to COVID-19 or other surrounding factors. Regardless of the answer, the diagnosis is complicated, and the mortality rate is high. Lessons: COVID-19 is posing a challenge to society, and new and unexpected diseases that had once disappeared have risen again. It is our duty to suspect them and to treat them in the most effective way possible.